THE RELATIONSHIP BETWEEN SCHOOL ORGANIZATIONAL CLIMATE AND PRIMARY TEACHER’S COMMITMENT IN MALAYSIA (Practitioner Research, 2023)
The purpose of this study was to examine the relationship between school organizational climate and teacher’s commitment. This study focused on four dimensions of school organizational climate which are institutional vulnerability, professional teacher, collegial leadership and achievement press. A quantitative survey method was applied and randomly tested with a sample of 170 teachers from seven government primary schools in the district of Arau, Perlis, Malaysia. The instrument used in this study was adapted from Organizational Commitment Questionnaire (OCQ) and the Organizational Climate Index (OCI). Analyses of the data gathered were presented using Statistical Package for Social Science (SPSS) version 21. The findings indicated that the relationship of school organization climate and teachers’ commitment is moderately strong.